You've got mail [videorecording (DVD)] - Ephron, Nora; Hanks, Tom; Ryan, Meg; Posey, Parker, 1968-; Stapleton, Jean, 1923-2013; Coleman, Dabney, 1932-; Kinnear, Greg, 1963- (Warner Home Video, 2001)
A romance in which superstore book chain magnate Hanks and cozy children's bookshop owner Ryan are anonymous e-mail cyberpals who fall head-over-laptops in love, unaware that they are combative business rivals.